香港电影之底层空间叙事 = Hong Kong movie : the narration of the lower class' living space - 吴金霏 Ng, Jin Fei (Nanyang Technological University, 2022)
本文以香港电影的底层空间为研究对象，探讨90年代以来香港底层社会的居住问题和生活状况的变化。接着，以香港底层的主流和边缘居住空间为例，分析政府土地政策和资本权力如何影响和压迫市民的生活。此外，本文将通过电影的空间选择和人物表现，分析导演如何结合在地经验和想象，诠释与再现底层的生活空间，重新描绘底层人民作为社会主体的重要存在。 关键词：香港电影；居住空间；底层；边缘 This paper aims to investigate the residential issues and living status of the lower social class in Hong Kong since the 1990s based on the portrayal of their living space in Hong Kong movies. Subsequently, by instances of the lower class' mainstream and fringe living spaces, the impact of the Hong Kong government's land policies and the power of capitalism on the citizens are analyzed. Furthermore, through the portrayed living spaces and characters in Hong Kong movies, this paper evaluates how movie directors tend to combine their personal local experience and imaginations to interpret and present the lower class' living space; as well as how they depict the importance of the lower class to the overall Hong Kong society. Keywords: Hong Kong movies; Living space; Lower class